Pengaruh Duta Merek, Citra Merek, dan E-WOM terhadap Keputusan Pembelian dengan Minat Beli sebagai Variabel Intervening: Studi pada Konsumen Somethinc di Kota Semarang - Anailul Rahmawati; Mahfudz Mahfudz (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to analyze the extent of the influence of brand ambassadors, brand image, and electronic word-of-mouth (e-WOM) on purchase decisions mediated by purchase intention. This study uses brand ambassadors, brand image, and e-WOM as independent variables, purchase decision as the dependent variable, and purchase intention as the intervening variable.Research data was obtained from 130 respondents who are Somethinc consumers in Semarang City through a questionnaire consisting of open and closed questions with a Likert scale of 1-5, which was then distributed online. Data analysis was carried out using the Structural Equation Model (SEM) method with AMOS software.The results of this study show that brand ambassadors have a positive and significant effect on purchase intention and purchase decision. Brand image also has a positive and significant effect on purchase intention and purchase decision. Similarly, e-WOM has a positive and significant effect on both purchase intention and purchase decision. Furthermore, purchase intention also has a positive and significant effect on purchase decision.